Remnant and the New Dark Age - Rommen, Edward 1947- (2021)
A new dark age has come upon us; as a result, Christianity and its churches in North America are no longer growing. One reason for this might be the widespread impression that Christians are hypocrites, saying they believe one thing while doing the opposite. However, that accusation would only be true if these believers actually believed the principles they are supposed to be violating. It is more likely that many Christians have, like those around them, abandoned truth in favor of personal opinion bringing moral discourse to a near standstill and intensifying the darkness by extinguishing the light of truth. Still, there is hope. In the past, it often was a faithful few, a remnant, who preserved the knowledge of that light and facilitated a new dawn. History shows us that the very movements that are today abdicating responsibility were once spiritual survivors themselves. They withdrew, coalesced around the remaining spark of truth in order to remember, preserve, and reignite. The thoughts and practices of these pioneers could guide the escape from today’s darkness.
Keywords: contemporary North American Christianity; Moral Discourse; remnant